Soil stabilization using eggshell powder and its effect on unconfined compressive strength (UCS) values - Mina, Enden; Kusuma, Rama Indera; Fathonah, Woelandari; Vindo, Alberto Dwi (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
Soil in road pavement construction has an important role as the foundation for the structure supporting the load above it. The damage that occurs in road construction also often due to subgrade soil that does not have good bearing capacity, therefore soil reinforcement or stabilization is needed to improve its strength. The road section in Cibingbin Village, Cibaliung subdistrict, Pandeglang Regency was damaged due to a lack of soil bearing capacity, where through field CBR tests it was discovered that the CBR value of the soil was 3% less than required. Soil strengthening can be done by adding additional substances to the soil which can increase its strength and bearing capacity. Eggshell powder was chosen in this research as an additive to see its effect on soil strength. Soil strength is tested through unconfined compression stress (UCS) testing in the laboratory. Apart from that, the effect of adding eggshell powder on the physical properties of the soil was also studied. Variations in adding eggshell powder were taken in varying percentages 0%, 2%, 4%, 6%, 8%, 10%, 12% and 14%. The results of testing the physical properties of the soil showed that the original soil type was classified as organic clay with high plasticity (CH). The UCS test results on the original soil had a strength (qu) value of 1.6 kg/cm2, and the adding eggshell powder could increase the qu value which got optimum value at the percentage 12% eggshell powder with 0 and 3 days of curing of 2.851 kg/cm2 and 3.386 kg/cm2 respectively. It can be concluded that the addition of eggshell powder can increase the soil strength. The consistency of the clay soil changes to become stronger and based on the UCS value the clay soil becomes stiffer.